Increased prevalence of subclinical atherosclerosis in patients with hidradenitis suppurativa (HS) - González-López, Marcos A.; Hernández, José L.; Lacalle, Marina; Mata, Cristina; López-Escobar, María; López-Mejías, Raquel; Portilla, Virginia; Fuentevilla, Patricia; Corrales, Alfonso; González-Vela, M. Carmen; González-Gay, Miguel A.; Blanco, Ricardo (Journal of the American Academy of Dermatology, 2016)
Chronic inflammatory diseases have been associated with increased prevalence of subclinical atherosclerosis. Hidradenitis suppurativa (HS) is a chronic inflammatory disease involving intertriginous skin. We sought to investigate the potential association between HS and subclinical atherosclerosis. This study included 68 patients with HS and 136 age- and sex-matched healthy control subjects. Patients with history of cardiovascular events, diabetes mellitus, chronic kidney disease, or another concomitant inflammatory condition were excluded. Carotid intima-media thickness and carotid plaques were measured by carotid ultrasonography. Adjustments were made for age, sex, and traditional cardiovascular risk factors. Patients had greater carotid intima-media thickness values than control subjects (0.615 ± 0.097 vs 0.578 ± 0.098 mm; P = .012). Carotid plaques were also more frequent in patients than in control subjects (30.9% vs 22.1%). In the multivariable regression model adjusted for age, sex, and traditional cardiovascular risk factors, HS was significantly related to the presence of carotid plaques (odds ratio 2.99, 95% confidence interval 1.26-7.13; P = .013). Causality could not be assessed. These results indicate an increased frequency of subclinical atherosclerosis in patients with HS. Accordingly, HS should be considered a disease associated with potentially increased cardiovascular risk.